Male-specific lethal 1 (MSL1) promotes Erastin-induced ferroptosis in colon cancer cells by regulating the KCTD12-SLC7A11 axis - Lifu Luo; Qingzhi Zhao; Xueli Cui; Shijiao Dong; Yong Wang; Nan Jiang; Chengyu Cai; Jingji Jin; Bing Liang (Cell Death and Disease)
Abstract MSL1, a scaffold protein of the MSL histone acetyltransferase complex, is crucial for its structural integrity and enzymatic activity. While MSL1 is highly expressed in various tumors, its role in tumor progression and cell death remains unclear. Here, we provide evidence of a negative regulatory relationship between MSL1 and KCTD12 through biochemical assays and knockdown/overexpression studies. Notably, in colon cancer cells, the ferroptosis inducer Erastin significantly suppressed MSL1 expression, leading to KCTD12 upregulation. Moreover, MSL1 promotes Erastin-induced ferroptosis in HCT116 and SW480 cells via the KCTD12-SLC7A11 axis. Consistently, Erastin-induced changes in ROS, GSH, and MDA levels were regulated by this axis, highlighting its role in ferroptosis. These findings offer potential therapeutic targets and a theoretical foundation for colon cancer treatment.